Technical feasibility study of floating solar power for water hyacinth removal in Limboto Lake, Gorontalo - Rifaldo Pido; Rahmat Libunelo; Rahmad Hidayat Boli (Jurnal Polimesin, 2025)
Limboto Lake in Gorontalo Province has experienced a decline in ecosystem quality due to the massive growth of water hyacinth (Eichhornia crassipes). The presence of water hyacinth reduces lake productivity and disrupts fishing activities. Common control efforts has been mechanical removal of water hyacinth with high cost due to fuel consumption. This study aims to assess the feasibility of utilizing a floating Solar Power Plant (PLTS) as an alternative energy source to power the water hyacinth lifting machine. The methods used in the study include a literature review, field surveys, calculations of engine energy requirements, design of a floating PLTS system, and technical feasibility analysis. The water hyacinth lifting machine requires 12–18 kWh of energy per day, which a floating PLTS system can meet with a capacity of 5 kWp. The findings demonstrate that the proposed floating solar power system is technically feasible for implementation. In addition to supporting the sustainable operation of water hyacinth-lifting machines, this technology also reduces evaporation from lakes and increases the use of renewable energy in Gorontalo.